Malayan-Chinese Interactions in Bangka from the Perspective of Symbolic Interactionism - Yuliarni, Yuliarni; Warto; Purwanta, Hieronymus (Komunitas: International Journal of Indonesian Society and Culture, 2024)
Bangka Belitung is recognized as a place where peace between Malayan and Chinese ethnic groups is upheld. Multifarious unique features emerge as the implication of cultural dialog between both groups. This study aimed to explore the meaningful relationship between Malayan and Chinese ethnic groups in Bangka from the symbolic interactionism perspective. The main foci are placed upon the roles of cultural symbols as a means to understand intercultural relationships. This study applied the qualitative method and ethnography approach, gathering data from the observation and interviews with people from both ethnic groups in Bangka. The result highlighted the importance of cultural symbolism in understanding the interaction between Malayan and Chinese people in Bangka. This study has contributed a deeper insight into the dynamics of interethnic interaction in Bangka, made meaning of quotidian life between Malayan and Chinese ethnic groups, and carried implications for interethnic and intersocial relationships. The key to strengthening interethnic relationships in Bangka is reconciliation and integration of cultural symbols.